Implementasi Load Balancing Dan Failover Pada Jaringan Internet Hotel Puri Indah Dengan Metode NTH - Ahmad Irpan Mawali; Ahmad Tantoni; Maulana Ashari (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Computer networks and the Internet are currently developing very rapidly, especially the role of the internet as a source of information, demanding excellent connection quality. Hotel Puri Indah Mataram, for example, has used two internet service providers (ISP) to handle the surge in demand from customers/guests. When there is an increase in requests, network devices become burdened because they have to process more requests. One solution is to implement load balancing, namely distributing the traffic load to network devices so that it is not centralized on just one ISP. This aims to ensure traffic runs optimally, increase throughput, speed up response time, and prevent overload on one connection line. This technique will optimize network performance by utilizing a two-path connection distribution method known as the NTH method. In addition, a failover technique will be implemented, where if one gateway connection is lost, another gateway will automatically take over all network traffic. This aims to ensure continuous service availability. Finally, there will be bandwidth management for all clients, so that bandwidth distribution becomes more even and efficient.